Analisis Gangguan Kecemasan Sosial Anak Berkebutuhan Khusus pada Usia Dini - Irma Nur Af'idah; Ilma Faza Rosyadah; Rika Amelia Putri (Tinta Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Early childhood has limited ability to think and move. But besides that, early childhood has rapid physical growth, as well as the basic abilities and skills that they develop. At a certain age, children have a selfish, stubborn, spoiled and sensitive attitude that is still very high. As parents, teachers and adults and their environment, we must understand the level of needs and character of children, so that there are no mistakes in educating and teaching. Because in the process of child development, needs will arise in the child that must be met and fulfilled. One of them is psychological need. These needs are absolutely necessary, and even play an important role in providing the basis for growth and development through physical, cognitive and socio-emotional aspects. When children have not received their needs properly, adjustment problems will arise in children, one of which is emotional and behavioral disorders. At each age level, children have different levels of needs, due to differences in age, physical, psychological, heredity and environmental factors. The needs of early childhood are closely related to the child's education process. The purpose of this study was to determine the needs and psychological disorders in early childhood through library research. This study uses research journals and books. Based on data analysis, it was found that there are several psychological needs that must be met for children as well as factors that cause children with psychological disorders.